See the Human behind the Law – The Court’s Perception of Neoslavery - Hrecska-Kovács, Renáta (The ECHR at 70: The Central European Narrative, 2025)
Forced labour is an economic activity that erodes human dignity. More than 300 cases on the prohibition of forced labour and slavery have so far been heard by the European Court of Human Rights (ECtHR), a number that suggests that fully topical human rights arguments can be made in this area. The relevant guidelines and legal texts of both the Council of Europe (COE) and the International Labour Organization (ILO) have served as a starting point for the present study, which has been supplemented with literature sources. This chapter presents the issue of the prohibition of forced labour in three major units. Firstly, the concept of forced labour is examined, then measures to combat the phenomenon, and finally the case law of the ECHR. The case law has been compiled to provide an overview of recent cases, mainly from theCentral European region.Keywords: forced labour, servitude, slavery, employment, freedom, equality, working conditions